2012
DOI: 10.1016/s1734-1140(12)70879-4
|View full text |Cite
|
Sign up to set email alerts
|

Mangiferin ameliorates 6-hydroxydopamineinduced cytotoxicity and oxidative stress in ketamine model of schizophrenia

Abstract: Mangiferin has a neurocytoprotective role related, at least in part, to an antioxidant and anti-inflammatory mechanism, which could be explored for more effective therapies of schizophrenia and other neurodegenerative diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 44 publications
3
26
1
Order By: Relevance
“…These differences can be evoked by different severity of clinical symptoms or duration of the schizophrenia. The study using magnetic resonance spectrometry showed either a fall of GSH in the cerebrospinal fluid and medial Ketamine-induced schizophrenia to mice " lipid peroxidation (brain) - [125] Ketamine-induced schizophrenia to mice " superoxide (prefrontal cortex) - [127] Ketamine-induced schizophrenia to rats " lipid peroxidation (cerebellum, prefrontal cortex, hippocampus, striatum, cortex) " protein peroxidation (striatum, hippocampus)…”
Section: Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences can be evoked by different severity of clinical symptoms or duration of the schizophrenia. The study using magnetic resonance spectrometry showed either a fall of GSH in the cerebrospinal fluid and medial Ketamine-induced schizophrenia to mice " lipid peroxidation (brain) - [125] Ketamine-induced schizophrenia to mice " superoxide (prefrontal cortex) - [127] Ketamine-induced schizophrenia to rats " lipid peroxidation (cerebellum, prefrontal cortex, hippocampus, striatum, cortex) " protein peroxidation (striatum, hippocampus)…”
Section: Clinical Studiesmentioning
confidence: 99%
“…In animal models of schizophrenia, perinatal phencyclidine (an NMDA receptor antagonist) administration increased the level of lipid peroxides in rats [124], while ketamine (an NMDA antagonist) injections to mice increased lipid [125,126] and protein [126] peroxidation and raised superoxide levels [127]. In genetic models, there were either increased levels of oxidized lipids in G72/G30 transgenic schizophrenic mice [128] or elevated cortical ROS production in g-aminobutyric acid-ergic interneuron-specific NMDAR hypofunction mice (Ppp1r2-Cre/ fGluN1 knockout [KO] mice) [129] (Table 1).…”
Section: Animal Studiesmentioning
confidence: 99%
“…Oxidative stress has been reported to modulate several behaviors including learning and memory function (Alzoubi et al, 2012; Alzoubi et al, 2013a; Alzoubi et al, 2013b), anxiety- (Allam et al, 2013; Hovatta et al, 2005; Masood et al, 2009; Salim et al, 2010a; Salim et al, 2011), depression- (Brocardo et al, 2012; Leonard and Maes, 2012; Pedreanez et al, 2011), mania- (Macedo et al, 2013), nociceptive- (Arcan et al, 2012) and schizophrenia- (Rao et al, 2012) like behaviors. We also measured the effect of social defeat-induced stress on oxidative stress within three critical brain areas, considered vital for depression, anxiety and cognition, namely, hippocampus, amygdala and prefrontal cortex (McEwen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A review from Mirza et al, 2013, also indicated that the antioxidant activity of MF is majorly contributed by catechol moiety (iron complexing capacity), which inhibit the production of free radicals by inhibiting the conversion of Fe 2+ to Fe 3+ complex and that would be the reason for maintaining the redox balance by elevating antioxidant status in MF treated pups. Supplementation of MF for 7 days probably eases oxidative stress and lipid peroxidation as well as protects BBB in schizophrenia mice model (Rao et al, 2012 Existing evidence suggest that impaired antioxidant with elevated free radicals (oxidative stress) and the neuroinflammatory response is considered to be the major reason for HIE (Sadeghnia et al, 2012;Slemmer at al., 2008). Both the events (oxidative stress and inflammation) are interconnected with one another.…”
Section: Groupmentioning
confidence: 99%